Letter: ciclosporin and vedolizumab for steroid‐refractory ulcerative colitis. Issue 3 (13th July 2020) - Resál, Tamás; Pigniczki, Daniella; Szántó, Kata; Rutka, Mariann; Farkas, Klaudia; Molnar, Tamas
Abstract : LINKED CONTENT This article is linked to Ollech et al paper. To view this article, visit https://doi.org/10.1111/apt.15616 .